Peningkatan Keandalan Berbasis Nilai Energy Not Supplied (ENS) Pada Penyulang Banyu Biru - Slamet Nurhadi; Mochammad Mieftah; Heri Sungkowo; Sukamdi (Politeknik Negeri Malang, 2024)
The reliability of the Banyu Biru feeder at PT. PLN (Persero) ULP Gondang Wetan is critical due to frequent disturbances causing significant energy losses and impacting SAIDI and SAIFI metrics. This study aims to enhance reliability by reducing ENS (Energy Not Served) values through strategic solutions. Data from March to August 2022 revealed 27 disturbances, comprising 6 permanent and 21 temporary interruptions. Initial calculations showed an ENS value of 20,509.84 kWh, a SAIDI of 0.24 hours/customer, and a SAIFI of 0.64 times/customer. The study proposed two scenarios: relocating the LBSM and adding 5 FCOs, and additionally installing a recloser in the second scenario. Post-implementation, ENS values decreased to 7,489.31 kWh, with SAIDI and SAIFI values improving to 0.08 hours/customer and 0.13 times/customer, respectively. These results highlight significant reductions in energy losses and improvements in network reliability, aligning with SPLN 68-2: 1986 standards. This research provides actionable insights for PT. PLN to enhance distribution network reliability and customer satisfaction.